FISHERMEN ALLEVIATION POVERTY MODEL IN THE NORTH COASTAL EAST JAVA - Roziana Ainul Hidayati; Mu'minatus Sholichah (Muhammadiyah University Press, 2011)
Poverty is a multidimensional problem that the approach to eradicate poverty must also be multidimensional. The study aims to formulate a model of poverty alleviation in coastal fishing in the North Coast of East Java. Grounded research approach used to determine the causes, impacts and implications of poverty fishermen. The results showed that the main cause of poverty that occurred in the three districts in East Java's north coast is different from one another. In Gresik district, the major cause of poverty is law enforcements that do not support fishermen and overfishing. While Lamongan more due to low fish prices and capital problems. While in Tuban fishermen due to limited infrastructure and lazy and extravagant lifestyle of the fishermen. These differences lead to different coping strategies so that later can form a concept model of poverty alleviation North Coast fishermen in East Java.